2
$\begingroup$

This problem

$$\lim_{x\to 0} \frac{\sqrt{\ 1+x} - \sqrt{\ 1-x}}{\sqrt[3]{\ 1+x} - \sqrt[3]{\ 1-x}}$$

is from Silverman's "Modern Calculus and Analytical Geometry" Section 22, #16d. I've been struggling on it for a while and can't figure out what to do besides trying to multiply by the conjugate and/or substitution but it doesn't work out. What do you all think? Keep in mind you can't use L'Hopital's rule, only elementary math.

$\endgroup$
  • 1
    $\begingroup$ $$ \Big( \sqrt[3]{1+x} - \sqrt[3]{1-x} \Big) \Big( \sqrt[3]{1+x}^2 + \sqrt[3]{1+x} \sqrt[3]{1-x} + \sqrt[3]{1-x}^2 \Big) = \Big( 1+x\Big) - \Big(1-x\Big). $$ That's how you would rationalize the denominator, if you do it that way. $\endgroup$ – Michael Hardy Sep 20 '17 at 2:05
8
$\begingroup$

Let $a=(x+1)^{1/6}$ and $b=(x-1)^{1/6}$. Then the expression becomes $\lim_{x→0}\frac{a^3-b^3}{a^2-b^2}$. This does divide through. It is equivalent to $\lim_{x→0}\frac{a^2+ab+b^2}{a+b}=3/2$.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Very nice solution! $\endgroup$ – Peter Szilas Sep 20 '17 at 6:40
3
$\begingroup$

Let $$a=(x+1)^{\frac{1}{6}}$$ $$b=(1-x)^{\frac{1}{6}}$$ Our equation becomes, $$\lim_{x\to 0} \frac{a^3-b^3}{a^2-b^2}$$ $$\lim_{x\to 0} \frac{(a-b)(a^2+ab+b^2)}{(a-b)(a+b)}$$

$$\lim_{x\to 0} \frac{a^2+ab+b^2}{a+b}$$$$\lim_{x\to 0} \frac{(x+1)^{\frac{1}{3}}+(1-x^2)^{\frac{1}{6}}+(1-x)^{\frac{1}{3}}}{(x+1)^{\frac{1}{6}}+(1-x)^{\frac{1}{6}}}$$$$\frac{1+1+1}{1+1}$$$$\frac{3}{2}$$

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

Added for your curiosity.

For the limit itself, you aleary received good answers. The problem can also be addressed using Taylor series or the generalized binomial theorem $$(1+x)^a=1+a x+\frac{1}{2} a(a-1) x^2+\frac{1}{6} a(a-1) (a-2) x^3+O\left(x^4\right)$$ making $$\sqrt{1+x}=1+\frac{x}{2}-\frac{x^2}{8}+\frac{x^3}{16}+O\left(x^4\right)$$ $$\sqrt{1-x}=1-\frac{x}{2}-\frac{x^2}{8}-\frac{x^3}{16}+O\left(x^4\right)$$ $$\sqrt[3]{1+x}=1+\frac{x}{3}-\frac{x^2}{9}+\frac{5 x^3}{81}+O\left(x^4\right)$$ $$\sqrt[3]{1-x}=1-\frac{x}{3}-\frac{x^2}{9}-\frac{5 x^3}{81}+O\left(x^4\right)$$ $$ \frac{\sqrt{\ 1+x} - \sqrt{\ 1-x}}{\sqrt[3]{\ 1+x} - \sqrt[3]{\ 1-x}}=\frac{ x+\frac{1}{8}x^3+O\left(x^4\right)} {\frac{2 }{3}x+\frac{10 }{81}x^3+O\left(x^4\right) }=\frac{3}{2}-\frac{13 x^2}{144}+O\left(x^3\right)$$ which shows the limit and how it is approached.

But what is interesting is that this is a very good approximation even if $x$ is not small. For example, using $x=\frac 12$, the exact expression is $\approx 1.47469$ while the approximation leads to $\frac{851}{576}\approx 1.47743$.

Edit

Making the problem more general and using the same steps $$\frac{(x+1)^p-(1-x)^p}{(x+1)^q-(1-x)^q}=\frac{p}{q}+\frac{p (p-q) (p+q-3)}{6 q}x^2+O\left(x^4\right)$$

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

\begin{align} & \lim_{x\to 0} \frac{\sqrt{1+x} - \sqrt{1-x}}{\sqrt[3]{1+x} - \sqrt[3]{1-x}} = \lim_{u,v\to1} \frac{u^3-v^3}{u^2-v^2} \\[10pt] = {} & \lim_{u,v\to1} \frac{(u-v)(u^2+vu+v^2)}{(u-v)(u+v)} = \lim_{u,v\to1} \frac{u^2+uv+v^2}{u+v} = \frac 3 2. \end{align}

Here of course $u = \sqrt{\sqrt[3]{1+x}} = \sqrt[6]{1+x}$ and $v=\sqrt{\sqrt[3]{1-x}}=\sqrt[6]{1-x}.$ An obvious qualm about this is that $\lim\limits_{u,v\to1}$ ought to mean a limit as the point $(u,v)$ approaches $(1,1)$ in the plane, whereas the two radicals do not approach $1$ independently of each other, but rather the pair moves along a particular curve. However, since we ultimately see that it does not matter along which curve $(u,v)$ approaches $(1,1),$ it follows that that does not alter the bottom line.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ The limit is $3/2$, not $0$. You have confused $u^{3/2}$ and $u$. $\endgroup$ – shalop Sep 20 '17 at 2:05
  • $\begingroup$ Haste makes waste. ok, I've cleaned this up somewhat. @Isham : You're quite right, except that I've made is $u^3-v^3$ in the numerator and $u^2-v^2$ in the denominator, since the point of the substitution was to get rid of radicals. $\endgroup$ – Michael Hardy Sep 20 '17 at 3:15
  • 1
    $\begingroup$ Thats funny you can consider that u --> v it works well $\endgroup$ – Aryadeva Sep 20 '17 at 3:42
2
$\begingroup$

$$\lim_{x\to 0}\frac{\sqrt{1+x}-\sqrt{1-x}}{\sqrt[3]{1+x}-\sqrt[3]{1-x}} = \lim_{x\to 0}\frac{\sqrt[3]{(1+x)^2}+\sqrt[3]{1-x^2} +\sqrt{(1-x)^2}}{\sqrt{1+x}+\sqrt{1-x}} = \frac{3}{2}.$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.